Permainan Tradisional sebagai Pengembangan Motorik Anak Sekolah Dasar - Yuzukka Ragil Septya Farida; Zihan Fathonah Ayuningsih; Anggara Dwinata; Muhammad Nuruddin (Edukasi Elita : Jurnal Inovasi Pendidikan, 2025)
Traditional games play an important role in the motor development of elementary school children. However, cultural changes and increasing use of technology have caused these games to be played less and less. This study aims to analyze the effect of traditional games on the motor development of elementary school children. Using a quasi-experimental method with a pretest-posttest control group design, this study involved 20 4th grade elementary school students who were divided into experimental and control groups. The experimental group was given treatment in the form of traditional games such as hopscotch, gobak sodor, and jump rope for 4 weeks. The results showed a significant increase in the gross motor development of children who participated in traditional games compared to the control group. In addition to motor benefits, traditional games also contribute to children's social, cognitive, and character development. Therefore, the integration of traditional games into the physical education curriculum in elementary schools is highly recommended to support children's holistic development.